The Effect Of Yoga Exercise On Anxiety In Third Semester Primigravida Pregnant Women - Sitorus, Riris; S, Grace Erlyn Damayanti; Ginting, Samuel; Diah Evawanna Anugerah (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2024)
Primigravida mothers are mothers who are experiencing pregnancy for the first time. Primigravida mothers are usually not ready to face pregnancy because it is something new to experience. The unpreparedness of primigravida mothers occurs both physically and psychologically. Anxiety is a feeling of discomfort manifested by restlessness, worry or fear. This is a manifestation of psychological and physiological factors. The third trimester is a time of alertness where at this time, pregnant women understand that their child can be born at any time. Mothers also feel impatient with the birth of the baby which makes mothers alert and vigilant. Anxiety during pregnancy can trigger changes in physical activity, sleep and nutrition. This can have an impact on fetal development and changes in the mother's mood. Yoga is a complementary therapy that can be an option to overcome anxiety in pregnant women, especially primigravida mothers in the third trimester. The design of this study was One Group Pretest and Posttest with the population being all primigravida pregnant women in the third trimester who checked their pregnancy at the Matahari Clinic. This study was tested on 17 samples taken using a purposive sampling technique. The results of the study showed that there was an average decrease in anxiety of 7.0000 and a p value of 0.000, which means that yoga exercises have an effect on reducing anxiety in pregnant women. So it is expected that midwives in the clinic are expected to apply yoga exercises to overcome anxiety in pregnant women, especially primigravida pregnant women in the third trimester.